Creating Digital Offerings Customers Will Buy - Ross, Jeanne; Beath, Cynthia; Mocker, Martin (MIT Sloan Management Review, 2019)
How can companies decide which new digital offerings to pursue? Successful digital offerings are created at the intersection of what technologies can deliver and what customers want and will pay for. That point of intersection, however, has proved to be elusive. To find it, companies must experiment repeatedly, cocreate with customers, and assemble cross-functional development teams - and the insights gleaned along the way must be shared internally.